Ergonomic Education and William Flexion Exercise Training for Low Back Pain Prevention Among Batik Artisans in Jarum Village, Klaten - Yuliani Setyaningsih; Hadi Sasana; Shofwan Bahar; Yesaya Rudolf Susanto Widyanto; Maxilla Narda Bentari; Nur Indah Komala; Stephen Arya Dwipa (Warta LPM, 2025)
Low Back Pain (LBP) is a prevalent occupational health complaint among batik artisans, resulting from static and non-ergonomic work postures. However, awareness regarding prevention and early management remains low, as these complaints are often normalized. This study aimed to evaluate the effectiveness of a targeted educational and practical training program on William Flexion Exercise in increasing knowledge about LBP prevention among batik artisans. The program applied a pre-experimental one-group pre-test post-test design involving 21 batik artisans. The intervention consisted of a socialization session on LBP and ergonomics, followed by a practical demonstration and training of the William Flexion Exercise. An increase in knowledge was measured using a questionnaire administered before and after the event. Data were analyzed using the non-parametric Wilcoxon Signed-Rank Test. The findings revealed an increase in the participants' mean knowledge score from 80.95 in the pre-test to 86.67 in the post-test. This increase was found to be statistically significant (W = 0.0; p = 0.031), with a large effect size (r = 0.88). The socialization and training program on the William Flexion Exercise was proven to be significantly effective in improving the knowledge of batik artisans regarding LBP prevention. The findings suggest that a community-based educational program incorporating practical exercise demonstration is a feasible and promising approach for increasing health knowledge. This model warrants further investigation in a larger controlled study.